(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
An analysis was conducted on the outcomes of conservative treatment for 30 children with exudative otitis media. Every patient received complete care, which included both mechanotherapy and medication. In accordance with a defined procedure (application No. 2014114122), extra immunocorrection was given to the observation group (n = 15) using the intranasal spray Imunofan. There was no immunocorrection administered to the comparison group (n = 15). After receiving Imunofan for one month, the clinical outcome—which was expressed in points based on questionnaire results—was 1.5 times better than that of the comparison group, and after three months, it was 2.1 times better. Upon reaching physiological norm levels, neutrophil myeloperoxidase activity under immunocorrection had significantly increased by the end of the first month (2.1 vs. 1.8) and the end of the third month (2.8 vs. 1.4).